A colorimetric and fluorescence sensor based on biphenolic-dansyl derivative for specific fluoride ion detection. Issue 5 (4th May 2021) - Mongkholkaew, Sitthichok; Songsasen, Apisit; Sirisaksoontorn, Weekit; Wannalerse, Boontana
ABSTRACT: 2ʹ-(2-((4-(methylthio)phenyl)amino)-2-oxoethoxy)-[1, 1ʹ-biphenyl]-2-yl 5(dimethyl amino)naphthalene-1-sulphonate (1 ) was synthesised and used as a F − ion sensor. The selectivity of sensor 1 with various anions (F −, Cl −, Br −, CH3 COO −, C6 H5 COO − and H2 PO4 − ) in DMSO was evaluated by 1 H NMR, UV-visible and fluorescence study. For 1 H NMR, an amide proton of sensor 1 disappeared due to the deprotonation reaction upon addition of F − ion. On the contrary, the proton signal of HF2 − emerged at 16.11 ppm. Upon addition of F − ion, sensor 1 showed a new absorption band at 300 nm and the solution turned colourless. For fluorescence response, sensor 1 exhibited the enhancement of emission intensity at 434 nm with slight blue shift when titrated with F − ion. These results suggest that sensor 1 possessed high sensitivity and selectivity towards F − ion detection. In addition, the sensor 1 test strip coated on TLC plates and filter papers were demonstrated for specific detection F − ion. Graphical abstract: uf0001